2019
DOI: 10.1155/2019/3186202
|View full text |Cite
|
Sign up to set email alerts
|

Fully Biobased Aliphatic Anionic Oligoesters: Synthesis and Properties

Abstract: Biobased aliphatic sulfonated oligoesters with 10 to 30% of sulfonated units were synthesized by melt polycondensation of biobased monomers such as diethyl succinate, z-octadec-9-enedioic acid, dimer fatty acid, sodium (sulfonated dimethyl succinate), and various diols like 1,4-butane diol and isosorbide. Structural characterization of the resulting oligoesters was determined by 1H NMR spectroscopy and MALDI-TOF MS technique. Showing a regular structure, the nature of the different expected species present in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…It is a very useful chemical intermediate because of its wide range of raw materials, chemical reactivity, good performance stability, and structural characteristics. DFA and its derivatives can be used to prepare polyamide resins, paint, lubricants, fuel additives, corrosion inhibitor, and other essential fine chemical products 31,32 . During UPR synthesis, introducing flexible macromolecular segments with reactive end groups, especially vegetable oils containing double bonds (such as DFA), can significantly improve the initial performance and impact resistance of UPR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a very useful chemical intermediate because of its wide range of raw materials, chemical reactivity, good performance stability, and structural characteristics. DFA and its derivatives can be used to prepare polyamide resins, paint, lubricants, fuel additives, corrosion inhibitor, and other essential fine chemical products 31,32 . During UPR synthesis, introducing flexible macromolecular segments with reactive end groups, especially vegetable oils containing double bonds (such as DFA), can significantly improve the initial performance and impact resistance of UPR.…”
Section: Introductionmentioning
confidence: 99%
“…DFA and its derivatives can be used to prepare polyamide resins, paint, lubricants, fuel additives, corrosion inhibitor, and other essential fine chemical products. 31,32 During UPR synthesis, introducing flexible macromolecular segments with reactive end groups, especially vegetable oils containing double bonds (such as DFA), can significantly improve the initial performance and impact resistance of UPR. Costa et al 33 reported the development of a new UPR based on soybean oil and coconut oil.…”
mentioning
confidence: 99%
“…1 H-NMR spectroscopy and MALDI-TOF MS of the resulting oligoesters highlighting a regular structure. The thermal properties indicate that the ensuing oligoesters are amorphous or semicrystalline that essentially depend on the nature of monomers [21]. On the other hand, polymers with ester and amide groups in their skeleton new opportunities for incorporating biodegradable and adequate performance properties in a single material.…”
Section: Introductionmentioning
confidence: 99%